Examining Dalit Experiences on English Language in Nepal: An Empowerment Perspective - Raj Paneru, Narendra; Bishwokarma, Babu Ram; Bahadur Bohara, Bhuban (Education and Development, 2026)
The role of the English language in Nepal can be observed from an inclusionary and exclusionary perspective in relation to the lives of Dalit individuals. In reference to this understanding, this study explores the interplay of caste-based discrimination and the role of the English language in Nepali society. Based on in-depth interviews with 12 participants-six Dalit students, two teachers, two policy actors, and two Dalit activists - the findings of the study show that the Dalits regard the English language as a tool for enhancing social mobility and demarginalization via effective communication and better job opportunities. On the other side, they are still enduring challenges like dehumanization, discrimination, and lack of financial capabilities for access to these opportunities. As English language learning is perceived as an elite expensive skill to achieve, financially constrained and socially marginalized Dalits have to face the threat of aggravation of their worse plight because of their compromised access to English. Thus, English, on the one hand is a symbol of hope and aspiration but at the same time, it may lead to exclusion.